Canine and feline uveal melanocytic tumours: Histologic and immunohistochemical characteristics of 32 cases. Issue 3 (5th February 2022) - Moreira, Matheus Vilardo Lóes; Langohr, Ingeborg Maria; Campos, Marina Rios de Araújo; Ferreira, Enio; Carvalho, Bárbara; Blume, Guilherme Reis; Montiani‐Ferreira, Fabiano; Ecco, Roselene
Abstract: Objective: Gross, histopathological, and immunohistochemical characteristics of uveal melanocytic neoplasms in dogs and cats were investigated. Samples: Thirty‐two enucleated globes with uveal melanocytic neoplasms, 27 from dogs and 5 from cats, were examined. Procedures: Morphological characteristics of uveal melanocytic neoplasms in dogs and cats were evaluated with anti‐PNL2, anti‐Melan‐A, anti‐Ki‐67, anti‐caspase‐3, and anti‐BAP1 immunomarkers. Statistical analysis was performed to compare canine melanocytomas and melanomas. Results: The 32 uveal neoplasms were classified as melanocytomas (19/27 in dogs) or melanomas (8/27 in dogs, 5/5 in cats). Most tumours (84%) were located in the anterior uvea. Neoplastic cells were classified as epithelioid, spindle‐shaped, mixed, or special type (balloon and signet ring cells). The percentage of cells with melanin, melanin concentration within cells, anisocytosis and anisokaryosis, mitotic count, lymphocytic inflammation, necrosis, vascular invasion, and glaucoma were also characterized. Anisocytosis, percentage of neoplastic cells with melanin, mitotic count, and indices (proliferation and apoptotic) varied significantly between canine uveal melanomas and melanocytomas; in general, melanomas had greater cell variability, were less pigmented, and had a higher mitotic count. The melanocytic origin of the neoplasms was confirmed by positive anti‐PNL2 immunolabelling (29/32) and positive anti‐Melan‐A immunolabelling (3/32). In canine uveal melanomas, anisocytosis and anisokaryosis correlated with less pigmentation and minimal pigmentation correlated with a high percentage of immunolabelling for caspase‐3. Conclusions: Uveal melanocytomas were more common in dogs, and uveal melanomas were more frequent in cats. Anisocytosis, percentage of neoplastic cells with melanin, and mitotic count are important histologic characteristics of malignancy to evaluate in uveal melanocytic neoplasms. The proliferation and apoptotic indices are relevant when comparing malignant tumours with benign tumours. Abstract :